Temporal case-based reasoning for reservoir spillway gate operation recommendation - Mohd Hassin, Mohd Hafiz; Md. Norwawi, Norita; Ab. Aziz, Azizi (2006)
In the traditional decision making process, in order to solve a problem, every possible solution will be generated and evaluated.The most optimum decision will be selected.However, this approach is unsuitable for urgent decision making, due to the time needed to evaluate all option. This project propose Temporal Case Based Reasoning (TCBR) technique to support dam technician in deciding which reservoir spillway gate will be opened or closed to release excess water in order to maintain a safe water level. Previous hydrological data of Timah Tasoh Dam, State of Perlis, Malaysia were used to develop the gate operation decision support model, which covers reservoir spillway gate operation activities from year 1998 to 2004. This model was then tested, and yielded up to 89 percent decision accuracy.